a THE EFFECT OF STOCK PRICE, TRADING VOLUME ACTIVITY, LIKUIDITY, RETURN AND STOCK RISK TOWARDS BID ASK SPREAD - srimutiaradewi@gmail.com mutiara dewi (Jurnal Kompetitif Bisnis, 2020)
This study aims to determinate the effect of the stock price, trading volume activity, liquidity, return and risk stock towards the bid-ask spread. This type of research is explanatory research. The population in this study are companies automotive sub-sector was listed in the IDX in 2019. The sampling technique used is purposive sampling and obtained as many as 10 companies automotive sub sector was listed in IDX in 2019. The data analysis technique used multiple regression panel data models and using the analysis tool eviews 9. The result shows that the variable trading volume activity has a significant effect on the bid-ask spread. stock price, liquidity, return, and risk stock not significantly influenced bid-ask spread. the period in a partial way. Based on the F test (simultaneous) shows that the stock price, trading volume activity, liquidity, return, and risk stock have a significant effect on the bid-ask spread.